(untitled) (Fiep Bulletin - online, 2013)
Considering that flexibility is an important component of human performance and fitness, and it is definitely incorporated to the Physical Education definitions in all areas, this study proposes a comparative analysis among the hip flexibility of 60 pre-pubescent children (ages 8-11) from both genders and different financial conditions, residents in the city of Teresina, Piauí State, who practice recreational activities. The children were divided into two equal-sized groups: children on low incomes (G1) and the children on higher than 4 minimum wages (G2). The “Seat and Reach” Test (Johnson; Nelson, 1979) proposed by Achour Junior (1999), was applied to evaluate the flexibility level of the children’s hamstrings. For the statistical analysis, a database was created in Microsoft Excel 2003 and the analysis was accomplished through SPSS 9.0. The results showed that there was a significant difference on the children’s flexibility level regarding the financial conditions. The group of children on low incomes (G1) presented a higher average (27.87 cm). As for gender, in a general way, the boys of the sample were more flexible (57.5% of boys and 45% of girls), it is due to the number of girls in the groups, which was smaller and, besides, in the G2 group only 33.33% of the girls reached the minimum criterion of 25 cm established by the Physical Best proposal (1988).